2019
DOI: 10.1128/jvi.00715-19
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Splice Variants of Zinc Finger Antiviral Protein (ZAP)

Abstract: Given the unprecedented scale of the recent Ebola and Zika viral epidemics, it is crucial to understand the biology of host factors with broad antiviral action in order to develop novel therapeutic approaches. Here, we look into one such factor: zinc finger antiviral protein (ZAP) inhibits a variety of RNA and DNA viruses. Alternative splicing results in two isoforms that differ at their C termini: ZAPL (long) encodes a poly(ADP-ribose) polymerase (PARP)-like domain that is missing in ZAPS (short). Previously,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(131 citation statements)
references
References 52 publications
11
120
0
Order By: Relevance
“…Further studies are required to elucidate the driving forces behind these changes and their effects on viral replication. It has been reported that the short isoform of ZAP can be induced by IFN in HEK293T and HeLa cells (31,32). Thus, the selective pressures to counteract ZAP might be higher in pathogenic infection associated with higher levels of immune activation and inflammatory cytokine expression.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to elucidate the driving forces behind these changes and their effects on viral replication. It has been reported that the short isoform of ZAP can be induced by IFN in HEK293T and HeLa cells (31,32). Thus, the selective pressures to counteract ZAP might be higher in pathogenic infection associated with higher levels of immune activation and inflammatory cytokine expression.…”
Section: Discussionmentioning
confidence: 99%
“…ZAPL and ZAPXL show higher antiviral activity against some viruses, but not all. All isoforms induce type I IFN expression similarly (Li et al, ).…”
Section: Trim25's Role In Innate Immunitymentioning
confidence: 99%
“…Since ZAP mRNA is multiply spliced [33], we considered that the mRNA splicing and processing factors that were positive hits in the RNAi screen might reduce ZAP as well as other host mRNAs. However, two different siRNAs to ISY-1 and SF3A1 that were shown to knockdown their targets did not knockdown ZAP or enhance replication of MVA in A549 cells.…”
Section: Plos Pathogensmentioning
confidence: 99%